Estrategias de comunicación y su influencia en la mejora de la imagen corporativa del Cetpro Computronic – ciudad de Huamachuco: 2018 - Villacorta Aguilar, Jorge Luis (2021)
This research study is based on an interrogative statement: What communication strategies influence the improvement of the corporate image of CETPRO COMPUTRONIC- city of Huamachuco: 2018 ?; It is a descriptive cross-sectional investigation, aimed at studies of internal clients and external potential clients, to collect the information two questionnaires were designed, which was applied for each type of clients, each questionnaire was divided into two parts; the first part aimed at auscultating communication strategies, and the second part aimed at the corporate image; As a consequence, the following conclusions were reached: advertising strategy, internet use, social media (Facebook, WhatsApp, etc.); as well as the traditional ones (radio, TV, Press); The promotional strategies, to grant scholarships, half scholarships, payment facilities; as the personal sales strategy: visit homes and schools, and as a public relations strategy, organize conferences, symposia, talks, etc. They are the ones that will improve the corporate image of CETPRO COMPUTRONIC. From the city of Huamachuco.